"Human" and "Divine" Lives in Book X of Aristotle’s Nicomachean Ethics - Konrádová, Veronika (ΠΗΓΗ/FONS, 2016)
The paper analyses the dual form of striving for a good life underlying Aristotle’s distinction between “human” and “divine” lives. The paper explores this theme with regard to the close connection between ethics and politics inherent in Aristotle’s analyses, focusing primarily on the specific relationship between politics and philosophy outlined in this connection in Book X of Aristotle’s Nicomachean Ethics. The distinction between political and philosophical life is interpreted not as a definition of two different life contents we are to choose from, but as a definition of two attitudes or perspectives our lives can be approached from – either from the perspective of a variety of different types of actions performed in the social space, or with regard to the unifying element binding our life together reflexively in a coherent whole. Taking into account the relevant principles of Aristotelian anthropology, the paper demonstrates that philosophical contemplation thus conceived is already grounded in political life and it does not stand against it as an option of some “other” life released from socio-political ties. The proposed interpretation makes it possible to alleviate the tension in Aristotle’s concept of political and philosophical life and thereby support a more coherent reading of the conclusion of the Nicomachean Ethics.